Robust handling of clumping and stiffness in wet hair animation - Kim, Jong‐Hyun; Kim, Wook; Kim, Young Bin; Im, Jaeho; Lee, Jung; Kim, Sun‐Jeong (Computer animation and virtual worlds, 2017)
Simulating the clumping and stiffness of wet hair or fur is a challenging problem. The dynamics of wet hair or fur are characterized by clumping and stiffness at the tip, which can be seen clearly in running animals or headbanging scenes. Existing animation methods address these phenomena within preset scenarios. However, there is no consensus on a method for depicting the details of wet hair. This paper therefore proposes a new method for modeling the clumping and stiffness of wet hair or fur. Previous studies have focused on modeling the absorption of water into hair or fur, whereas this paper considers a realistic simulation of wet hair. Unlike dry hair strands, wet hair strands adjacent to one another are subject to a clumping force, gathering together and becoming more stiff as the saturation level of water increases. The proposed method builds on a surface‐tension model based on smoothed particle hydrodynamics to simulate the clumping force and to adjust the hair elasticity via stiffness constraints. The method gives realistic simulations of wet hair by maintaining the clumping force of the wet hair during movement and by simulating the stiffness of the hair in line with its water‐saturation level. This paper proposes a new method for modeling the clumping and stiffness of wet hair or fur. Previous studies have focused on modeling the absorption of water into hair or fur, whereas this paper considers a realistic simulation of wet hair. Unlike dry hair strands, wet hair strands adjacent to one another are subject to a clumping force, gathering together and becoming more stiff as the saturation level of water increases.